Students' Politeness to Lecturers in WhatsApp Application Measured Using Leech Maxim - Nurdiyani, Netty; Sasongko, Sasongko (State institute of islamic studies salatiga, 2022)
This study aims to describe student politeness in communicating or sending messages to lecturers through the Whatsapp application. This research needs to be carried out to obtain an overview of the application of politeness principles used by students in communicating. This research is descriptive qualitative research with instrumental case studies, the instrument used is Maxim Leech. The source of this research data is student texts sent to lecturers. The research data are sentences, phrases, or words that contain aspects of politeness by Leech's politeness principles. Data retrieval uses the note-taking method, while data analysis uses the high method. The basic analysis technique is a technique for direct elements that sorts text into several categories of data forms, namely sentences, clauses, phrases, and words. The results of this study indicate that all politeness maxims are not used by students in sending student Whatsapp messages to lecturers. . From the six Maxim Leech Principles, five of them are used by students in communication. The five maxims are tact maxim, approbation maxim, modesty maxim, generosity maxim, and agreement maxim. Of the five maxims used, the modesty maxim is most widely used compared to the other maxims. This shows that the politeness of students in a humble attitude exceeds other politeness. Research on student politeness can still be developed both in theory, methodology, and the depth of the discussion Keywords: politeness, WhatsApp, online learning